Critical discourse analysis of Martin Luther's speech - Zeeshan Ali (Journal of Education, Social & Communication Studies, 2024)
This study aims to critically examine Martin Luther’s speech through the lens of Critical Discourse Analysis (CDA), focusing on the interaction between language and societal factors such as race, social class, and identity. By analyse the speech at the word, text, social, and discursive levels, this research seeks to uncover the ways in which Luther’s rhetoric reflects and influences the socio-political context of his time. The study employs a descriptive and qualitative methodology, utilizing historical transcripts as the primary data source. At the micro-level, the analysis emphasizes lexical features and transitivity, while the macro-level analysis explores grammatical, social, ideological, and discursive characteristics. The findings reveal that Luther’s strategic use of language not only challenged the dominant ideologies of his era but also played a significant role in shaping the Reformation movement. The study concludes that Luther’s speech serves as a powerful example of how discourse can be used to both reflect and enact social change.